Literature Review: The Relationship Between Tea Dringking Habits and The Incident of Anemia in Pregnant Women - Mulya, Ketrin Permata; Hardisman, Hardisman; Yulizawati, Yulizawati (Universitas Andalas, 2025)
Background: Pregnancy anemia is condition when the hemoglobin (Hb) less than 11 g/dL. Based on the Indonesian Healthy Survey in 2023, the prevalance of pregnancy anemia was 27,7%. One of the risk factors was excessive consumption of tea, because it contained tannins that inhibited iron absorption.Purpose: The purpose of this study was to determine the relationship between tea drinking habits and the incidence of anemia in pregnant woman.Methods: This type of research was a literature review with a scoping review method, conducted from March 2024 to March 2025. Data were collected through digital database sources, namely: Pubmed Central, Sciencedirect, Google Scholar, DOAJ, and Garuda, published from 2019-2024. Data were analyzed using thematic analysis.Results: Relevant articles was selected based on inclusion and exclusion criteria, and processed usinh the PRISMA-ScR flow diagram. 21 articles were identified for analysis. 21 articles were analizied by thematic analysis.Conclusion: The study show, that the habit of drinking tea is associated with the incidence of anemia during pregnancy. The frequency of daily tea consumption with an amount of 1, 2, or 3 cups causes anemia and the timing of tea consumption before, after or with meals within a time span of up to 1 or 2 hours is also associated with pregnancy anemia